GOVERNMENT PUBLIC RELATIONS STRATEGY TO IMPROVE WEST BANDUNG PERCEPTION USING 4C CONCEPT - Ramadhanty, Dini Siti; Rachman, Reza Saeful; Evert, Daniel Paulus; Mulyono, Tanto Trisno; Annash, Puan Arsi (PT Altin Riset Publishing, 2025)
This study aims to determine the impact of Instagram social media management on improving the reputation of the West Bandung Regency Government. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman analysis model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the management of the Instagram account @prokompim_kbb is aimed at building and enhancing the positive image of the West Bandung Regency Government. The strategies employed are based on Chris Heuer's 4C theory, namely: Context, Communications, Collaborations, and Connections. First, context plays a crucial role in message formation, specifically how narratives and captions are crafted using appropriate and effective language to align with the information being conveyed. Second, communications emphasize the importance of internal communication before content is published to ensure the content and purpose of the message are consistent. Third, collaborations are carried out through cooperation between the @prokompim_kbb admin and all regional and village government agencies in producing relevant content. Fourth, connections are established by forming WhatsApp groups and conducting technical guidance sessions with social media administrators at the regional and village levels to strengthen communication networks and social media management capabilities. Overall, social media management based on the 4C concept has proven effective in supporting efforts to enhance the reputation of local governments through digital platforms.